CURRICULUM FOR PEACE EDUCATION AND NATIONAL DEVELOPMENT AT THE TETIARY EDUCATION LEVEL - Obeka, Ngozi O.; Nwigwe, N (EBSU Journal of Social Sciences and Humanities, 2024)
This paper is an attempt to examine the curriculum for peace education and national development at the tertiary education level. Peace education is aimed at inculcating in the mind of learners the knowledge, skills and capabilities to pursue peace and to respond to conflicts and crisis in a non-violent way. Curriculum for peace education has to do with the integration of peace education and concepts into the goals and objectives of learning at all levels of tertiary education programme in order to equip the students with requisite knowledge, skills and capabilities to not only cultivate a lifestyle of peace but to opt for dialogue and peaceful resolution of conflicts. The aims and objectives of peace education were elaborated. Peace education curriculum at the tertiary education level was also explored. Then, the impact of peace education on national development was investigated. Approaches to peace education instruction were also enumerated. Finally, the role of the lecturer in the curriculum for peace education at the tertiary education level was examined. Based on the issues examined, one of the recommendations is that peace education should be integrated into the curriculum of tertiary education in all the departments, especially the general education courses.